Efektivitas Metode AMT (Achievement Motivation Training) guna Meningkatkan Perilaku Asertif Siswa SMP Muhammadiyah 04 Singosari - Anggraini, Shalsabillah Indah; Ma’mun, Muhammad Jamaludin; Widodo, Rinto Wahyu (Sahabat Publikasi, 2024)
Passive behavior in learning occurs a lot among Indonesian students, based on the results of pre-research conducted by researchers by interviewing teachers and also students of Junior High School Muhammadiyah 04 Singosari during the pre-research showed that 80% of students were less assertive. The purpose of this research is to find out whether the AMT (Achievement Motivation Training) method can increase students' assertive behavior. This research is included in the experimental research with pretest-posttest control group design experimental design. The population in this study was grade 9 Junior High School Muhammadiyah 04 Singosari, and the samples taken in this study totaled 37 students and used a sampling technique with saturated samples. Analysis of the results of the study using the normality test and T-test using SPSS. Based on the results of data collection, it was found that the normality test was 0.200 > 0.05 so the pre-test and post-test values were normally distributed. The results of the T-test were 0.31 > 0.05, which means that there were differences in the post-test results of the two groups that were given treatment and were not given treatment. So the AMT method is effective in increasing assertive behavior.